Clinical outcomes of endoscopic mucosal resection and endoscopic submucosal dissection as a transoral treatment for superficial pharyngeal cancer. Issue 9 (1st September 2012) - Hanaoka, Noboru; Ishihara, Ryu; Takeuchi, Yoji; Suzuki, Motoyuki; Uemura, Hirokazu; Fujii, Takashi; Yoshino, Kunitoshi; Uedo, Noriya; Higashino, Koji; Ohta, Takashi; Kanzaki, Hiromitsu; Hanafusa, Masao; et al.
Abstract Background Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) have been introduced for the treatment of superficial pharyngeal cancer. Methods Sixty superficial pharyngeal cancers in 45 patients were treated by EMR or ESD. Resectability and curability, complications, and survival were analyzed retrospectively. Results The en bloc resection and curative resection rate were higher with ESD (100; 81.6%) than with EMR (59; 50%). In subgroup analysis with regard to tumor size ≤10 mm, both resection rates were comparative. All the patients had preserved larynx and swallowing, speech, and airway function. Two of the 45 patients died of other diseases, local recurrence was observed in 4 of 18 patients with noncurative resection with a median observation period of 38 months. No recurrence was observed in patients with curative resection. Conclusions ESD or EMR for superficial pharyngeal cancer is minimally invasive treatment and lesions larger than 10 mm should be referred for ESD. © 2012 Wiley Periodicals, Inc. Head Neck, 2013